Advanced membrane technology for biomass separation - Lau, Adrian Chee Yang (Nanyang Technological University, 2024)
Single cell proteins (SCP) are becoming increasingly popular today as an alternative source of protein, given that current sources of protein are largely unsustainable. SCPs are derived mainly from microorganisms that undergo fermentation to produce products that have a solids content of under 5%. To extract the pure SCPs, further separation techniques are required which include coagulation and flocculation, sedimentation, floatation, centrifugation, and membrane filtration. Among these methods, membrane separation is most favored due to its advantages such as carrying out separation processes without the need for additives, relatively low energy consumption, and continuous separation at mild conditions.